Evodiamine derivatives improve cognitive abilities in APPswe/PS1ΔE9 transgenic mouse models of Alzheimer's disease. Issue 2 (29th June 2020) - Pang, Shuo; Sun, Caixian; Gao, Shan; Yang, Yajun; Pan, Xiandao; Zhang, Lianfeng
Abstract: Background: Alzheimer's disease (AD) is a complex neurodegenerative disease. Due to the complexity of its molecular pathogenesis and the interaction of the numerous factors involved, the etiology and pathogenesis of AD have not been fully elucidated. Therefore, effective treatment for AD remains to be developed. Evodiamine, a quinolone alkaloid, has been found to improve learning and memory ability to in the APP swe /PS1 △E9 mouse model of dementia. However, the cytotoxicity and physicochemical properties of evodiamine have limited its use in the treatment of AD. Methods: Evodiamine and its derivatives were effectively synthesized by EDCI‐mediated condensation at room temperature. These target compounds contained 1 thio‐ and 21 oxo‐evodiamine derivatives with different substituted groups. The cytotoxicity of evodiamine and its derivatives and the neuroprotective effects of the evodiamine derivatives against H2 O2 ‐induced cell loss in SH‐SY5Y cells were investigated using the WST‐8 assay. The Morris water‐maze test was used to detect the effect of evodiamine and its derivatives on improving learning and memory in APP swe /PS1 △E9 mice. Results: In this study, a series of oxo‐ and thio‐evodiamine derivatives was synthesized. Several derivatives showed lower cytotoxicity and stronger neuroprotective effects than evodiamine and elicited enhanced cognitive improvement, especially in the test of spatial memory in APP swe /PS1 △E9 mice. Conclusion: Our study provides insights for developing novel evodiamine derivatives for chemical intervention and treatment of AD.